2018
DOI: 10.22370/bolmicol.2018.33.1.1164
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and growth-effects of ectomycorrhizal fungi of a Nothofagus pumilio forest in the Andes of Southern Chile

Abstract: Chilean temperate rainforests have unique climatic, edaphic and biotic conditions, constituting pre-industrial blueprint ecosystems. Mycorrhizal associations play a central role in the biogeochemical processes of these ecosystems´ functioning. Baseline forest ecology studies are necessary in order to better understand diversity patterns, specifically regarding mycorrhizal symbiosis. Therefore, here we describe the vegetation characteristics and the mycorrhizal relationships of vascular plants in a Nothofagus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…These dwarfed, multistem trees exhibited higher leaf nutrient content coupled with increased rates of nutrient movement between roots and shoots. Our results support previous evidence that ECM associations adapted to high elevations and low soil pH may facilitate N accessibility at high elevations (Moeller et al ., ; Marín et al ., ). Both Clavulinaceae and Cortinariaceae were particularly abundant at the treeline (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…These dwarfed, multistem trees exhibited higher leaf nutrient content coupled with increased rates of nutrient movement between roots and shoots. Our results support previous evidence that ECM associations adapted to high elevations and low soil pH may facilitate N accessibility at high elevations (Moeller et al ., ; Marín et al ., ). Both Clavulinaceae and Cortinariaceae were particularly abundant at the treeline (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…We consider spore inoculation is the most realistic option for local nurseries that probably cannot afford the cost of mycelium production or purchase. Nonetheless, EcM taxa other than those proposed here have been reported from nurseries and naturally established Nothofagaceae seedlings as Descolea (Palfner et al, 2008;Valenzuela Flores et al, 2008;Álvarez et al, 2009;Fernández et al, 2015;Salgado Salomón et al, 2018a), Hebeloma (Fernández et al, 2015;Salgado Salomón et al, 2018a), Sebacina, Inocybe, Laccaria, Genea (Fernández et al, 2015;Marín et al, 2018), Tomentella (Kuhar et al, 2016;Fernández et al, 2013Fernández et al, , 2015Salgado Salomón et al, 2017, 2018a, Clavulinaceae (Fernández et al, 2015), Thelephorales (Fernández et al, 2015), Pyrenomataceae (Fernández et al, 2013;Salgado Salomón et al, 2018a). To broaden the perspective of EcM species best suited to inoculate nursery plants, especially for those with low fruiting frecuency, small spores production or corticioid habit, mycelium inoculum production, mycorrhizal infection and field performance tests will be required.…”
Section: Forestrymentioning
confidence: 55%
“…Further studies need to incorporate these rhizospheric interactions when accounting for the AMF community composition and its effects on bamboo plant growth and other ecosystem processes. Also, when prospecting micro-propagation efforts of bamboo, the local AMF community should be taken into account, as local and specific mycorrhizal fungi may have better results on plant growth and survival than non-local and non-specific mycorrhizal fungi (Marín et al 2018); this specificity may be reflected on this study, as the AMF genus Sclerocystis was found in only one rhizospheric soil sample of A. verticillatum (Table 2). The northern and central areas of Brazil have been extremely understudied in terms of mycorrhizal ecology and biodiversity (Bueno et al 2017), albeit noticeable exceptions (de Assis et al 2018;Marinho et al 2019), most research has been concentrated in natural and agricultural ecosystems of the southern part of the country (Bueno et al 2017;Davison et al 2015).…”
Section: Discussionmentioning
confidence: 99%